Is it true that what you can't see can't hurt you?. (July 2015) - Larson, Dave; Gates, Stephen
Abstract : Trying to establish when the acronym 'DDoS' (Distributed Denial of Service) was very first used is not as easy as you might think. According to various sources, the first usage of the term 'denial of service' was in 1997; a special report to the President's Commission on Critical Infrastructure Protection was released by the Software Engineering Institute at Carnegie Mellon University (which would later become part of CERT). 1